2003
DOI: 10.1042/bst0311032
|View full text |Cite
|
Sign up to set email alerts
|

Binding properties and anti-bacterial activities of V-region identical, human IgG and IgM antibodies, against group B Neisseria meningitidis

Abstract: We have constructed chimaeric (ch) mouse/human antibodies with identical binding regions isolated from the V-genes of two mouse parent hybridoma cell lines, with specificity against the P1.7 and P1.16 epitopes on the outer-membrane protein PorA on meningococci. The chimaeric antibodies can be used to analyse relationships between specificity, binding activity (avidity and kinetics), isotype (antibody class and antibody subclass) and in vitro anti-bacterial activity of meningococcal antibodies. The antibody set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…At low complement concentrations (Ͻ10%) activation of complement occurs mainly through the classical pathway (59). However, previous studies comparing monoclonal IgG and IgM antibodies against meningococcal surface PorA protein revealed IgM to be more active than IgG in OPA under conditions similar to those used in the present study (29,30). Also, when different concentrations of complement serum were tested with a human monoclonal IgM anti-P1.…”
Section: Discussionmentioning
confidence: 97%
“…At low complement concentrations (Ͻ10%) activation of complement occurs mainly through the classical pathway (59). However, previous studies comparing monoclonal IgG and IgM antibodies against meningococcal surface PorA protein revealed IgM to be more active than IgG in OPA under conditions similar to those used in the present study (29,30). Also, when different concentrations of complement serum were tested with a human monoclonal IgM anti-P1.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, a conformational change in this loop may affect the relative orientation of the CH1 domain versus the Fc, thereby influencing effector binding to the Fc. There are now many examples of Abs with identical variable domains but different isotypes that bind the same Ag with a different affinity or specificity (13,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Some of these studies suggested that the CH1 domain accounts for the observed changes in binding, because it was identified as the only region with sequence diversity between the tested Abs and because a similar effect was observed using only the Fab instead of the entire Ab scaffold (13,16,19).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent reports provide some evidence for binding-related allosteric effects in Abs. It was demonstrated that Ag binding, as well as the structure of the variable domains, may be influenced by changes in the constant domains (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). For example, Pritsch et al (13) demonstrated that two human mAbs sharing identical variable domains, but expressing different isotypes, bind tubulin with significantly different affinities.…”
mentioning
confidence: 99%
“…In one study, all three IgG1 anti-PorA MAbs tested had superior bactericidal activity to the respective IgG3 MAbs (28), while in the second study an IgG1 anti-PorA MAb had similar or better activity than the IgG3 MAb (37). The second study also investigated the activity of a chimeric IgG2 anti-PorA MAb, which had less activity than the IgG1 or IgG3 MAbs, while the IgG4 MAb with identical respective V region genes had no activity.…”
Section: Discussionmentioning
confidence: 99%